Distribution of M1 and M2 macrophages in tumor islets and stroma in relation to prognosis of non-small cell lung cancer - Jackute, Jurgita; Zemaitis, Marius; Pranys, Darius; Sitkauskiene, Brigita; Miliauskas, Skaidrius; Vaitkiene, Simona; Sakalauskas, Raimundas (BMC immunology, 2018)
Non-small cell lung cancer (NSCLC) remains the most common cause of cancer related death worldwide. Tumor-infiltrating macrophages are believed to play an important role in growth, progression, and metastasis of tumors. In NSCLC, the role of macrophages remains controversial; therefore, we aimed to evaluate the distribution of macrophages (M1 and M2) in tumor islets and stroma and to analyze their relations to patients' survival. Lung tissue specimens from 80 NSCLC patients who underwent surgical resection for NSCLC (pathological stage I-III) and 16 control group subjects who underwent surgery because of recurrent spontaneous pneumothorax were analyzed. Immunohistochemical double staining of CD68/iNOS (markers for M1 macrophages) and CD68/CD163 (markers for M2 macrophages) was performed and evaluated in a blinded manner. The numbers of M1 and M2 macrophages in tumor islets and stroma were counted manually. Predominant infiltration of M1 and M2 macrophages was observed in the tumor stroma compared with the tumor islets. M2 macrophages predominated over M1 macrophages in the tumor tissue. Tumor islets-infiltrating M1 macrophages and the number of total tumor-infiltrating M2 macrophages were independent predictors of patients survival: high infiltration of M1 macrophages in tumor islets was associated with increased overall survival in NSCLC (P < 0.05); high infiltration of total M2 macrophages in tumor (islets and stroma) was associated with reduced overall survival in NSCLC (P < 0.05). This study demonstrated that high infiltration of M1 macrophages in the tumor islets and low infiltration of total tumor-infiltrating M2 macrophages were associated with improved NSCLC patients' survival. ClinicalTrials.gov NCT01955343 , registered on September 27, 2013.